Effects of selected oils as natural preservatives on chemical Quality and shelf life of beef kofta - Sabry, Reham; Abou El Roos, Nahla A.; Ibrahim, Hemmat M. (Journal of Advanced Veterinary Research, 2024)
Preservatives of natural sources have become a seemingly better and safer than artificial preservatives. Since these preservatives come from plants, they don’t have negative side effects like artificial preservatives. This study investigated the effects of Laurel nobilis, Moringa oleifera and Olive oils at different concentrations on the sensory attributes and chemical quality of beef Kofta at 4°C for 10 days cold storage period. Results revealed that samples treated with 1% Moringa, 0.5 % Moringa and 1% olive oils maintained the overall acceptability until 10th days of cold storage while those treated with 1 % laurel, 0.5 % laurel and .05 % olive oils got spoiled at 10th day. On the other hand, control samples got spoiled at 8th day of cold storage. Samples treated with selected oils showed marked decrease in their chemical analysis pH, Thiobarbituric Acid (TBA) and Total Volatile Basic Nitrogen (TVB-N). These results indicating that these oils have potent antioxidant effects. Best antibacterial and antioxidant results were obtained in samples treated with 1% Moringa oleifera oil followed by those treated with 1% olive oil then Laurel oil at 0.5% which showed the lowest results with accepted sensory properties. On the other hand, Laurel oil 1% is more effective as antibacterial and antioxidant and demonstrated more enhancements of sensory attributes. So, the results suggested that Laurel oil 1%, Moringa oil 1% and Olive oil 1% can be applied to beef kofta as natural preservatives.